Brief Considerations Regarding Special Criminal Offences Committed against the Financial Interests of the European Union - Getty Gabriela Popescu; Florin Tudor; Andreea Elena Matic (Communications of International Proceedings, 2021)
As a member state of the European Union, Romania has ensured a proper legal protection of the European Community’ financial interests by adapting the legal frame in order for the authorities to be able to identify and punish the criminal offences committed against the European Community financial interests. In the present paper we aim to analyze the content and the enforcement of the criminal offence of using or presenting in bad faith, inaccurate or incomplete documents or declarations which result in the illegal diminution of the resources which are to be transferred to the general budget of the European Union or to the budgets administered by it or on its behalf, enshrined by the criminal law. The actual application of the criminal law in this matter has raised several issues as a number of interpretations of the incriminating rules have emerged, especially with regard to the criminal offences that ensure the protection of the European Community financial interests, an area in which there is no case law yet. In our research we will refer to these types of particular cases and interpretations.
Keywords: European Union; budget; financial interests of EU; criminal offence; criminal law